2020
DOI: 10.1111/beer.12270
|View full text |Cite
|
Sign up to set email alerts
|

Leading with moral courage: The interplay of guilt and courage on perceived ethical leadership and group organizational citizenship behaviors

Abstract: This study uses a moderated mediation model to investigate the role of leaders’ moral courage and guilt in promoting group‐level organizational citizenship behavior (OCB). Based on the idea that leaders model ethical behavior among followers, we examine whether leaders’ display of morally laden emotions weaken follower perceptions of ethical leadership, thus disrupting the influence of moral courage on followers. Two independent studies examined the proposed model. Study 1 used an experimental design to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 83 publications
2
26
0
5
Order By: Relevance
“…To solve ethical problems and to fulfill the moral quest of the profession, nurses need moral courage. 3 However, a copious number of studies have evidenced that nurses suffer from unresolved ethical problems causing them moral distress with adverse consequences. 4 , 5 Thus, nurses need a climate that enables them to meet their role and foster resolving these ethical problems; this is called ethical climate.…”
Section: Introductionmentioning
confidence: 99%
“…To solve ethical problems and to fulfill the moral quest of the profession, nurses need moral courage. 3 However, a copious number of studies have evidenced that nurses suffer from unresolved ethical problems causing them moral distress with adverse consequences. 4 , 5 Thus, nurses need a climate that enables them to meet their role and foster resolving these ethical problems; this is called ethical climate.…”
Section: Introductionmentioning
confidence: 99%
“…Positive perceptions of organizational virtues also lead to greater employee engagement, translating into organizational citizenship behaviors [28]. Likewise, Mansur, Sobral, and Islam [80] found a positive association between an ethical (virtue-based) leadership and organizational citizenship behaviors. From there, the fifth research hypothesis is based: Hypothesis 5 (H5).…”
Section: Organizational Virtues and Organizational Citizenship Behaviorsmentioning
confidence: 95%
“…By testing a multilevel model of mediation, Ruiz-Palomino, Linuesa-Langreo, and Elche [84] found a mediating role of organizational citizenship behaviors in the relationship between leadership and team performance, ratifying the positive association between leadership and organizational citizenship. Moreover, Mansur et al [80] found a positive association between ethical (virtue-based) leadership and organizational citizenship behaviors. In the same perspective, Nemr and Liu [32] concluded that ethical leadership has both direct and indirect effects on organizational citizenship behaviors, signaling the importance of studying variables that mediate the relationship between leadership and organizational citizenship behaviors, as we examined in the present study.…”
Section: Organizational Virtues Human Resources Management Practices and Organizational Citizenship Behaviorsmentioning
confidence: 99%
“…If leaders want their officers to do the right thing, no matter what, when interacting with the public, then the leaders have to model moral courage. For example, in one study that used a non-police sample, it was found that “courageous leaders are able to inspire and encourage followers to act prosocially” ([ 64 ], p. 597). Within police agencies, although this remains to be empirically tested, it can be assumed that leaders who demonstrate moral courage will have officers who are more likely to maintain a strong service orientation, despite the challenges.…”
Section: Leadership and Maintaining A Culture Of Wellnessmentioning
confidence: 99%